2014
DOI: 10.1002/ejoc.201402079
|View full text |Cite
|
Sign up to set email alerts
|

Straightforward Synthesis of Various 2,3‐Diarylimidazo[1,2‐a]pyridines in PEG400 Medium through One‐Pot Condensation and C–H Arylation

Abstract: PEG400 is described herein as a suitable medium for the condensation of various 2‐amino pyridines with α‐bromo ketones. 2‐Arylimidazo[1,2‐a]pyridines were synthetized in a short time through microwave irradiation in moderate to excellent yields. After optimization, a convenient one‐pot process enabled access to 2,3‐diarylimidazo[1,2‐a]pyridines by using a reduced amount of palladium catalyst without ligand for the C–H arylation step in the same environmentally‐sound medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 53 publications
(8 reference statements)
0
22
0
Order By: Relevance
“…1 H-NMR of the isolated product showed a remarkable singlet at δ = 8.20 ppm for the imidazole proton. The high value of such a chemical shift indicated that this =CH is adjacent to a sp 3 hybridized nitrogen atom [26,27], which is possible in isomer 6A rather than isomer 6B . As illustrated in Scheme 2, the reaction proceeds via the formation of an iminothiadiazole intermediate I , followed by in-situ dehydrative cyclization to form the desired fused heterocycle 6A [19].…”
Section: Resultsmentioning
confidence: 99%
“…1 H-NMR of the isolated product showed a remarkable singlet at δ = 8.20 ppm for the imidazole proton. The high value of such a chemical shift indicated that this =CH is adjacent to a sp 3 hybridized nitrogen atom [26,27], which is possible in isomer 6A rather than isomer 6B . As illustrated in Scheme 2, the reaction proceeds via the formation of an iminothiadiazole intermediate I , followed by in-situ dehydrative cyclization to form the desired fused heterocycle 6A [19].…”
Section: Resultsmentioning
confidence: 99%
“…In 2014, Berteina-Raboin et al generated 2-arylimidazo[1,2-a]pyridines in good yields within 10 minutes from readily available 2-amino pyridines and α-bromo ketones. A one-pot procedure was engineered to achieve 2,3-diarylimidazo[1,2-a]pyridines using a reduced amount of palladium catalyst without ligand for the C-H arylation step in the same environmentally sound medium (Scheme 52) [96]. In 2014, Berteina-Raboin et al, generated 2-arylimidazo[1,2-a]pyridines in good yields within 10 minutes from readily available 2-amino pyridines and α-bromo ketones.…”
Section: Reactions In Pegmentioning
confidence: 99%
“…Pursuing our objective of the development of new practices in the synthesis of heterocycles containing oxygen, sulfur and nitrogen, [3][4][5][6][7][8] we explored the potentialities of eucalyptol as a solvent in the Buchwald-Hartwig coupling reaction. This work began with a literature review to identify the best conditions for this kind of transformation.…”
Section: Introductionmentioning
confidence: 99%